Os desafios da coleta seletiva e a necessidade de organização dos catadores de materiais recicláveis na cidade de Uberlândia - Fernandes, Anderson César (2020)
Among the countless challenges faced by Brazilian’s municipalitiescities, as in the case of Uberlândia, is the management of waste, driven by the economic growth of cities, which has led to an increased of supply of goods and services and, consequently, consumption and the amount of waste produced. However, this brought great concerns about the preservation and maintenance of the natural environment. Thus, it is necessary for municipal administrations to pay more attention about the waste management, which involves control over their production, storage, collection, separation, transport, treatment and disposal. It happens that one of the great collaborators in this process is the collectors of recyclable materials through the selective collection that amins to give a correct destination for the residues. However, for this to happen within the legal framework, these workers must leave informality and provide services through the signing of agreements with the public entity. But, since December 2016, with the end of the agreement concluded with the Municipality of Uberlândia and with the advent of Law 13.019/14, the associations and cooperatives of recyclable material collectors in Uberländia faced a series of challenges that needed to be overcome so the work could be developed within the legal framework and so this way they could leave informality. Therefore, this work points out some suggestions based on the trajectory of solid recyclable waste management in the city of Uberlândia - MG, in this way these challenges can be overcome. In addition of this, it is important to emphasize that there is a need for the effectiveness and dissemination of public policies adopted by the Municipality of Uberlândia, because a large part of the population still unaware of the programs adopted by the municipality of Uberlândia in relation to selective waste collection.